TINJAUAN LITERATUR MENGENAI DAMPAK PENGELOLAAN RISIKO DALAM PENGENDALIAN INTERN TERHADAP PRILAKU TERKAIT SISTEM INFORMASI AKUNTANSI - Amelia Setiawan (Center for Economic Studies Universitas Katolik Parahyangan, 2012)
The aim of this article is to examine prior studies on riskmanagement impact to internal control. Risk management is related to internal control systems and behavior. The behavior investigated in this article is accountants’ behavior about disclosure in financial reporting. The methods og this article is literature review form published article in international journal.Keywords: risk management, internal control, accountants’behavior, accounting information systems